Russian civil society actors in exile: An underestimated agent of change - Maria Domańska (Stiftung Wissenschaft und Politik (SWP), 2023)
The current wave of emigrants from Russia can play an important role in the country's political transition in the long term. As Russia's aggressive wars are a consequence of the personalist dictatorship that has embraced the imperialist idea, a regime change towards a more pluralistic model of rule would be in the West's strategic interest.
Keywords: 320; Russia; emigrants; political transition; Ukraine invasion; repression against the democratic opposition; civil society; NGOs; Alexei Navalny